Effect of Ultra-Processed Foods Consumption on Sleep Disturbances Among Brazilian Adults’ Population: A Propensity Score Matching Approach - Olivares-Tirado, Pedro; Zanga, Rosendo (Journal of Sleep And Sleep Disorder Research, 2023)
Background Diet, exercise and sleep are three pillars of a healthy life. These lifestyle factors influence one another in complex and dynamic ways. Consistent evidence exists about the bidirectional relationship between sleep patterns and food intake. Objectives We aim to assess the effect of the ultra-processed food(UPF) consumption on sleep disturbances in a sample of the Brazilian adults. Method We analyzed 77,298 persons aged 18 and older from the Brazilian National Health Survey (2019). A Propensity Score Matching (PSM) approach was used to address confounding bias and balance the matched exposed and control groups. The population average treatment effect (PATE) and the population average treatment effect on the treated (PATT) were estimated. Also, the Absolute Risk Increase and the Relative Risk Increase were computed. Results The findings revealed that Brazilian adults who consumed UPF experienced small but statistically significant sleep disturbances compared to non-UPF users. Furthermore, salty UPF showed small but significant worsening of sleep compared to sweet UPF users. Conclusion The consumption of UPF is associated with sleep disturbances in Brazilian adults. The consumption of salty UPF had a more significant effect on sleep disorders than sweet UPF in the overall population. However, among individuals who already consumed sweet or salty UPF, these foods had a more significant effect on sleep disorders. To gain a deeper understanding of the complex relationship between UPF consumption, sleep disorders, and their impact on health and quality of life, further research is needed, including precise measurements and consideration of personality traits using prospective designs.
Keywords: Sleep; sleep disturbances; ultra-processed foods; Brazilian population; propensity score.